Pengelolaan Limbah B3 di Rumah Sakit Gigi dan Mulut Universitas Padjadjaran Kota Bandung - Eka Wardhani; Fitra Akbar Kamil (Jurnal Serambi Engineering, 2020)
This study aims to identify and evaluate the management of toxic and hazardous materials (THM) at Universitas Padjadjaran (Unpad) Dental Hospital. This hospital is a special teaching hospital to support the teaching and learning process at the Faculty of Medicine Unpad. Based on the results of observations, THM were produced as much as 322.96 kg/month. The waste generation includes infectious, sharp objects and pharmaceutical waste. The research was conducted by using a comparison method between the conditions at the research location and the applicable regulations. Based on the results of research, the Dental and Oral Hospital Unpad has carried out the management of THM in accordance with applicable regulations. There are several aspects that must be improved, namely the process of sorting and packaging of THM, and attaching symbols and labels to containers. Temporary shelters for THM are operating properly according to the criteria, but there are several things that need to be improved, namely routinely replacing damaged labels because they can cause misinformation about these THM. Shelters need to be equipped with cooling devices, improve ventilation, and establish good trench drainage while THM increasing.